Experimental quasi-static axial crushing of cone–tube–cone composite system - Mahdi, E; Hamouda, A.M.S; Sahari, B.B; Khalid, Y.A (Elsevier, 2003)
An experimental investigation was carried out to study the crashworthiness parameters of cone-tube-cone composite system. The quasi-static crushing behaviour of axially compressed cone-tube-cone composite system has been investigated experimentally. The conical parts of composed system were symmetric. The cone vertex angles used were 10 and 15°. Two arbitrary cone ratios of height-to-base-diameter (C/D1) have been explored. The tubular part heights were varied between 0 and 50 mm and between 0 and 20 mm for 1.41 and 0.69 of C/D1 ratios, respectively. Load-displacements curves and deformation histories of typical specimens are presented and discussed. The results showed that structures with ratios (tube-height-to-total-height) vary between 0.06 and 0.11 exhibit a higher crashworthiness performance.